2014
DOI: 10.1152/jn.00663.2013
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of cat paw trajectory during locomotion

Abstract: We investigated which of cat limb kinematic variables during swing of regular walking and accurate stepping along a horizontal ladder are stabilized by coordinated changes of limb segment angles. Three hypotheses were tested: 1) animals stabilize the entire swing trajectory of specific kinematic variables (performance variables); and 2) the level of trajectory stabilization is similar between regular and ladder walking and 3) is higher for forelimbs compared with hindlimbs. We used the framework of the uncontr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 71 publications
2
18
0
Order By: Relevance
“…6). As others have proposed (Hollands and Marple-Horvat 1996;Klishko et al 2014;Patla and Vickers 2003) and based on our results, it is likely that paw placement at contact is planned before swing onset. Initial position of the paw at swing onset does not appear to be a factor in determining paw placement at contact because the transition from stance to swing occurred with the paw positioned more caudally with increasing speed (Fig.…”
Section: Stride Lengthsupporting
confidence: 69%
See 2 more Smart Citations
“…6). As others have proposed (Hollands and Marple-Horvat 1996;Klishko et al 2014;Patla and Vickers 2003) and based on our results, it is likely that paw placement at contact is planned before swing onset. Initial position of the paw at swing onset does not appear to be a factor in determining paw placement at contact because the transition from stance to swing occurred with the paw positioned more caudally with increasing speed (Fig.…”
Section: Stride Lengthsupporting
confidence: 69%
“…The position of the paw at contact is arguably the most important event in the step cycle because it is critical to maintain dynamic stability (Halbertsma 1983;Klishko et al 2014). Here we show that placement of the hind paw relative to the hip at contact in chronic spinalized adult cats is invariant across speeds for both the left and right sides (Fig.…”
Section: Stride Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…The task is formed at cortical levels while the few-to-many mappings rely significantly on subcortical structures. These may involve the spinal cord as suggested by recent observations of multi-joint synergies stabilizing paw trajectory during locomotion of intact cats and induced locomotion in spinalized cats (Klishko et al, 2014a,b). Future systematic studies of the neural control of movement stability in animal models, healthy humans, and different neurological disorders may help us to understand the neural substrates of ICS, assist the lesion localization, and development of treatment strategies.…”
Section: The Role Of Central Nervous System In Icsmentioning
confidence: 90%
“…This find is in line with the present literature on the topic. Namely, over the course of the last 30 years, the work of Irina Beloozerova and her lab has demonstrated that higher centers of motor control, such as the motor cortex and basal ganglia, are most implicated in task that require precise limb manipulations during locomotion 235,236,249,250 . Furthermore, studies by Trevor Drew et al have also demonstrated that the dorsiflexor related function during the production of obstacle avoidance trajectories is most significantly impaired following the GABA-receptor agonist muscimol injections to the motor cortex in the cat 221 , which is a comparable manipulation to that of transient ischemic ablation of the motor cortex.…”
Section: The Hemiparetic Strategy Lies Close To An Alternative Solutimentioning
confidence: 99%